Design and Analysis of a Wide-Band Printed Fractional Antenna for Medical and Internet Equipment Applications - صالح السموءل; علي صادق; سعيدي امجد (Latakia University Journal -Engineering Sciences Series, 2021)
Printed antennas are considered to be one type of the most common antennas in the field of wireless communication, as they are widely used in internet equipment and wireless medical equipment, due to their simple structure, low cost and good gain. Internet equipment and wireless medical equipment are characterized by their high sensitivity in transmitting data, and in the accuracy of manufacturing their printed circuits, therefore the antenna used in such equipment is considered an essential component, and must be characterized by the best parameters in terms of gain, directivity, radiation energy and quality. This paper presents a design for a wide-band printed fractional antenna operating in several frequency fields, suitable for internet and wireless medical applications within the range of (1-10) GHZ, by using fractional engineering, that provides a multi-dimensional structure, in order to generate different resonant frequencies according to the effective lengths in this structure. The aforementioned antenna was designed and analyzed using HFSS (High Frequency Structure simulation), which is considered as a virtual lab, that allows to perform a large number of tests, which saves time and cost, until reaching the appropriate design for the required application. This simulator allows the analysis of all the antenna parameters such as frequency, gain, bandwidth, radiation pattern and reaching frequency response.